Pendidikan Karakter Berbasis Kearifan Lokal Melalui Nangun Sat Kerthi Loka Bali - Ni Putu Candra Prastya Dewi (Edukasi: Jurnal Pendidikan Dasar, 2020)
Degradation of character appears to be the abandonment of local cultures by being replaced by foreign cultures which actually have a negative impact on the development of Indonesia's young generation, especially in Bali. Therefore it is necessary to have a character education based on local wisdom so that the younger generation does not forget the Balinese culture. The vision of the government that fosters local wisdom-based character is "Nangun Sat Kerthi Loka Bali". Through this vision, the provincial government of Bali issued a number of policies relating to the preservation of Balinese culture from the day of the use of traditional Balinese clothing, the implementation of the Balinese language month, to the use of local Balinese products. If this policy is carried out by all Balinese people on a continuous basis, it will shape the habits of the community which in turn can also shape character.  Keywords: character education, local wisdom, Nangun Sat Kerthi Loka Bali